Canthin-6-one induces cell death, cell cycle arrest and differentiation in human myeloid leukemia cells - Vieira Torquato, Heron F.; Ribeiro-Filho, Antonio C.; Buri, Marcus V.; Araújo Júnior, Roberto T.; Pimenta, Renata; de Oliveira, José Salvador R.; Filho, Valdir C.; Macho, Antonio; Paredes-Gamero, Edgar J.; de Oliveira Martins, Domingos T. (Biochimica et biophysica acta. General subjects, 2017)
Canthin-6-one is a natural product isolated from various plant genera and from fungi with potential antitumor activity. In the present study, we evaluate the antitumor effects of canthin-6-one in human myeloid leukemia lineages. Kasumi-1 lineage was used as a model for acute myeloid leukemia. Cells were treated with canthin-6-one and cell death, cell cycle and differentiation were evaluated in both total cells (Lin+) and leukemia stem cell population (CD34+CD38−Lin−/low). Among the human lineages tested, Kasumi-1 was the most sensitive to canthin-6-one. Canthin-6-one induced cell death with apoptotic (caspase activation, decrease of mitochondrial potential) and necrotic (lysosomal permeabilization, double labeling of annexin V/propidium iodide) characteristics. Moreover, canthin-6-one induced cell cycle arrest at G0/G1 (7μM) and G2 (45μM) evidenced by DNA content, BrdU incorporation and cyclin B1/histone 3 quantification. Canthin-6-one also promoted differentiation of Kasumi-1, evidenced by an increase in the expression of myeloid markers (CD11b and CD15) and the transcription factor PU.1. Furthermore, a reduction of the leukemic stem cell population and clonogenic capability of stem cells were observed. These results show that canthin-6-one can affect Kasumi-1 cells by promoting cell death, cell cycle arrest and cell differentiation depending on concentration used. Canthin-6-one presents an interesting cytotoxic activity against leukemic cells and represents a promising scaffold for the development of molecules for anti-leukemic applications, especially by its anti-leukemic stem cell activity. [Display omitted] •Canthin-6-one induces cell death with apoptotic and necrotic characteristics in AML cell line.•Cell cycle arrest induced by canthin-6-one was concentration-dependent.•Canthin-6-one reduces leukemic stem cell population and elicits cell differentiation in AML lineages.